Efektivitas Terapi Akupunktur dalam Meningkatkan Nilai IQ (Intelligence Quotient) pada Mahasiswa Jurusan Akupunktur Politeknik Kesehatan Surakarta - Joko Tri Haryanto; Risna widowati (Jurnal Terapi Wicara dan Bahasa, 2022)
Abstract Intelligence Quotient or commonly referred to as IQ is a term for grouping human intelligence which is believed to be a standard measure of intelligence for many years. One aspect of intellectual intelligence is memory. Some students who study in the Acupuncture Department find it difficult to memorize the lessons in the Acupuncture Department. The lack of research on the effects of acupuncture therapy in increasing a person's IQ score is the reason for the authors to conduct this study. This study aims to determine the effectiveness of acupuncture therapy in increasing the IQ (intelligence quotient) in students of the Acupuncture Department of the Health Polytechnic of Surakarta. This research is a pre-experimental pre-test and post-test design. The research will be conducted at the D-III Acupuncture Study Program in collaboration with the psychotest organizing institution, namely ANAVA Surakarta. The subjects of this study were 30 students of the Department of Acupuncture. The dependent variable is the Intelligence Quotient (IQ) score and the independent variable is acupuncture therapy at points HT 7 (Shenmen), GV 20 (Baihui), PC 6 (Neiguan) and SP 6 (Sanyinjiao). Data analysis using paired t test. There is a difference in mean IQ scores before and after acupuncture treatment. The mean value after acupuncture increased (mean=108) compared to the mean before acupuncture therapy (mean=101). Based on the analysis of the paired t test, the value of p <0.05 was obtained, which means it can be concluded that acupuncture therapy is effective in increasing the IQ (Intelligence Quotient) value. Acupuncture therapy is effective in increasing the IQ (Intelligence Quotient) in Acupuncture Department students.